Impact of the COVID-19 Outbreak on Disease Spectrum of Pediatric Intensive Care Units - Li, Wen Jing; Xue, Chun Ling; Li, Zhuo (Frontiers in Medicine, 2022)
Purpose: We aimed to analyze the changes in the disease spectrum data of a pediatric intensive care unit (PICU) in Nanjing, China, during the coronavirus disease (COVID-19) outbreak and explore a feasible plan for the treatment of critically ill children. Methods: This retrospective study used data of our PICU from January 1, 2018, to December 31, 2020. Patient demographics, distribution of disease spectrum, results of etiological examinations, and the PICU length of stay (LOS) were compared during the COVID-19 period (2020) and the previous years (2018 and 2019). Results: In 2020, the number of PICU admissions was 46.8% and 47.8% lower than that in 2018 and 2019, respectively. There were significant differences in the number of PICU patients of different age groups, and these differences were mainly found in children aged less than 4 years and older than 14 years. The percentage of the number of PICU patients with respiratory diseases decreased significantly, while those with hematological diseases, poisoning and rare diseases increased significantly. Moreover, the number of patients with rare diseases increased significantly, while the number of patients with mitochondrial diseases exceeded that of those with autoimmune encephalitis. The PICU LOS in 2020 was higher than that observed in 2018 and 2019, indicating that the changes in the PICU disease spectrum did not directly affect the PICU LOS. Etiological examinations revealed that during the COVID-19 period, the number of PICU patients with bacterial infections increased, those with viral infections decreased, although not statistically significant. Conclusions: A striking decrease in the number of PICU admissions was observed during the COVID-19 outbreak, which caused a significant change in the PICU disease spectrum. Changes in the number and characteristics of patients admitted to PICUs should be considered for facilitating the effective working of PICUs during the COVID-19 pandemic.